Testing the cosmic conservation of photon number with type Ia supernovae and ages of old objects - Jesus, J. F. [UNESP]; Holanda, R. F.L.; Dantas, M. A. (Springer Nature, 2017)
In this paper, we obtain luminosity distances by using ages of 32 old passive galaxies distributed over the redshift interval 0.11 < z< 1.84 and test the cosmic conservation of photon number by comparing them with 580 distance moduli of type Ia supernovae (SNe Ia) from the so-called Union 2.1 compilation. Our analyses are based on the fact that the method of obtaining ages of galaxies relies on the detailed shape of galaxy spectra but not on galaxy luminosity. Possible departures from cosmic conservation of photon number is parametrized by τ(z) = 2 ε z and τ(z) = ε z/ (1 + z) (for ε = 0 the conservation of photon number is recovered). We find ε=0.016-0.075+0.078 from the first parametrization and ε=-0.18-0.24+0.25 from the second parametrization, both limits at 95% c.l. In this way, no significant departure from cosmic conservation of photon number is verified. In addition, by considering the total age as inferred from Planck (2015) analysis, we find the incubation time ti n c= 1.66 ± 0.29 Gyr and ti n c= 1.23 ± 0.27 Gyr at 68% c.l. for each parametrization, respectively.
Keywords: Cosmic opacity; Galaxy ages; Scale distance; Type Ia Supernovae